Cutting Edge: NADPH Oxidase Modulates MHC Class II Antigen Presentation by B Cells (2012)
ABSTRACT: Phagocyte NADPH oxidase plays a key role in pathogen clearance via reactive oxygen species (ROS) production. Defects in oxidase function result in chronic granulomatous disease with hallmark recurrent microbial infections and inflammation. The oxidase’s role in the adaptive immune response is not well understood. Class II presentation of cytoplasmic and exogenous Ag to CD4+ T cells was impaired in human B cells with reduced oxidase p40phox subunit expression. Naturally arising mutations, which compromise p40phox function in a chronic granulomatous disease patient, also perturbed class II Ag presentation and intracellular ROS production. Reconstitution of patient B cells with a wild-type, but not a mutant, p40phox allele restored exogenous Ag presentation and intracellular ROS generation. Remarkably, class II presentation of epitopes from membrane Ag was robust in p40phox-deficient B cells. These studies reveal a role for NADPH oxidase and p40phox in skewing epitope selection and T cell recognition of self Ag.